The Implementation Of Knowledge Strategies For Competitive Advantage In Selected Malaysian Government- Linked Companies - Helmi, Asleena (2013)
The case study had included thirty-three interviews among the four GLCs and adopted a post-positivist approach via the triangulation of multiple resources namely interview findings, document and literature review. The problem being investigated was on why knowledge strategy (KS) was significant to the government-linked companies (GLCs) in Malaysia. Proposition one of the study stated that the implementation of KS was significant to the GLCs in order to achieve competitive advantage. The main factors which contributed to the successful implementation of KS that were investigated in this study were the levels of dynamic capability (DC); interorganizational relations (IOR) and value propositions namely the ‘knowledge value added’ (KVA) approach. The third proposition focused on analyzing any inherent KS differences being implemented by the GLCs; the application of the KVA approach indicated that the ratio of knowledge (ROK) among the four GLCs differed based on different levels of key performance indexes. The cases were found to have differed in the levels of KS maturity which illustrated the inherent differences in the KS being implemented by the GLCs. Based on the KPMG maturity model (1999), that the GLCs had achieved either pre-innovative or advanced stages allowing companies to identify where they stand in their KM journey and what initiatives or further steps of improvement the company to be considered. The findings from the case study were able to support the culmination of these three propositions.